PENGARUH GCG, FREE CASH FLOW, DAN OWNERSHIP STRUCTURE PADA PERUSAHAAN MANUFAKTUR - Jerry Budiman; Linda Santioso (Jurnal Paradigma Akuntansi, 2022)
This study aims to test empirically the influence of Board Size, Board Independence, Board Meetings, Free Cash Flow, Ownership Concentration, and Managerial Ownership on Corporate Performance in manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2019 period. The sample was selected by purposive sampling method and the data used were 71 companies. The test method used in this study is linear regression using the EViews 10 software. Based on the results of the research that has been done, it can be concluded that Free Cash Flow has a positive effect on Corporate Performance, while Board Size, Board independence, Board Meetings, Ownership Concentration and Managerial Ownership have no influence on Corporate Performance.The implication of this research is that large amounts of free cash flow can help improve company performance.